Some remarks on the beheading iconography from the lands between the Taurus and Greater Caucasus - Dan, Roberto; Cesaretti, Andrea (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
This article examines the complex subject of iconographic representations of beheading. This topic is found in various areas of the Near East from at least the Neolithic; several recent overall studies have systematized this information. The paper discusses a number of archaeological finds with different versions of decapitation iconography from areas located to the north and east of Mesopotamia. These objects were produced over a long period spanning from the Middle Bronze Age to the Iron Age. The study demonstrates that the theme of beheading, with all of its related implications, relates to not only Mesopotamia and the Syrian-Levantine area but also territories beyond these areas.